1990
DOI: 10.1152/ajprenal.1990.258.1.f162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endothelium-derived relaxing factor and nitric oxide on rat mesangial cells

Abstract: We have investigated whether endothelium-derived relaxing factor (EDRF) and nitric oxide (NO), a substance proposed to be one of the EDRFs, could elicit biochemical and biological responses in rat glomerular mesangial cells (MC). In wells with MC alone, guanosine 3',5'-cyclic monophosphate (cGMP) levels were 2.6 +/- 0.6 fmol/microgram protein, and bradykinin did not affect these levels, whereas in coincubation experiments with bovine aortic EC and rat MC, cGMP levels in MC increased to 44.6 +/- 21 fmol/microgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
81
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 0 publications
5
81
0
Order By: Relevance
“…In a preliminary study, 42 bradykinin, a known substrate for NEP in vitro, 2 released endothelium-derived relaxing factor and thereby stimulated soluble guanylate cyclase activity and cGMP production in rat mesangial cells. Although the effects of bradykinin on urinary cGMP excretion in vivo have not been demonstrated, previous studies have shown that SQ 29,072 did not potentiate the depressor activity of bolus injections of bradykinin in conscious SHR.…”
Section: Discussionmentioning
confidence: 96%
“…In a preliminary study, 42 bradykinin, a known substrate for NEP in vitro, 2 released endothelium-derived relaxing factor and thereby stimulated soluble guanylate cyclase activity and cGMP production in rat mesangial cells. Although the effects of bradykinin on urinary cGMP excretion in vivo have not been demonstrated, previous studies have shown that SQ 29,072 did not potentiate the depressor activity of bolus injections of bradykinin in conscious SHR.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, as the example of nifedipine il lustrates, drug-specific intrarenal effects may antag onize a BP-dependent antiproteinuric action and even counteract the effect of lowering systemic BP. 24,81 On the other hand, the lack of effect of nifedipine on albumin excretion may depend, perhaps in part, on proximal tubular inter actions. 46 Nifedipine caused a marked reduction in fractional lithium reabsorption and a corresponding increase in lithium clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The recent finding that bradykinin increases cyclic GMP and inhibits the contractile response of mesangial cells to Ang II when added to coincubations of mesangial and endothelial cells supports this possibility. 37 The fall in preglomerular resistance seen during the infusion of the kinin antagonist may be secondary to the fall in K { and partial compensation via the rubuloglomerular feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%